Contraception within six-month postpartum in rural Vietnam: Implications on family planning and maternity services - Duong, Dat Van; Lee, Andy; Binns, Colin (Taylor & Francis Group, 2005)
Objectives: This longitudinal study documents contraception practice and factors influencing contraception decision within the first six months postpartum, amongst women residing in the rural Northern Central region of Vietnam.Methods: A sample of 463 rural women who gave birth during August-October 2002 were recruited and interviewed at one, 16 and 24 weeks postpartum.Results: The proportion of contraceptive users at weeks 16 and 24 were 17% and 43% respectively. At week 24, of contraceptive users, 57% used IUD, 25% used condom, and 14% used traditional methods. Logistic regression analysis found age, sufficient knowledge on contraceptives and husband/partner opinion can significantly affect the contraception decision.Conclusions: In order to improve the situation, health authorities should be encouraged to provide counselling on postpartum contraceptive methods during ante- and postnatal care visits. Health education on family planning and breastfeeding should also involve the husband/partner group taking into account local socio-cultural features.